Capitalismo, trabalho e formação profissional: dilemas do trabalho cotidiano dos assistentes sociais em Ribeirão Preto - SP - Tinti, Élidi Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper aims to discuss existing dilemmas in professional work of the social worker, inserted in different areas, in the light of academic formation that occurred at different times for each professional and considering the determinations of bourgeois daily sociability. The study was conducted from the reflection on the work category and on the settings of the working world, analyzing the specificities of the Brazilian situation and inserting the social worker in his social, political and economic context as a worker. Then the reflection includes the analysis on the formation of social workers from the settings of the current higher education policy in Brazil. This analysis covers the study of development of social work and the construction of the theoretical-methodological apparatus of the profession, as well as existing problems regarding the relation between theory and practice. Eight social workers were interviewed in Ribeirão Preto, active in socio-legal, health, social assistance and social welfare areas. From the considerations made in the light of the theoretical discussion and the content of the interviews, this study discusses the conflicts experienced by the professionals interviewed in their daily professional work, emphasizing the difficulties in relation to the theoretical and methodological referential, that guides and contemplates the vision of the same about their education, their working conditions and the Brazilian situation. Throughout the study it was revealed that the configurations of formation and the objective conditions of the reality that social workers are working interfere directly in their perceptions on the issues, determining a context that does not identify a specific theoretical and methodological framework and sets a guidance practice in various conflicts as regards theory and practice relationship. The importance of continued formation were noted as something extremely important for professionals...

O presente trabalho se propõe a discutir os dilemas existentes no trabalho profissional do assistente social, inserido em diferentes áreas de atuação, à luz da formação acadêmica ocorrida em diferentes momentos para cada profissional e considerando-se as determinações da sociabilidade burguesa para o trabalho cotidiano. O estudo foi realizado a partir da reflexão sobre a categoria trabalho e sobre as configurações do mundo do trabalho, analisando-se as especificidades da conjuntura brasileira e inserindo o assistente social neste contexto social, político e econômico enquanto um trabalhador. Em seguida a reflexão abarca a análise sobre a formação profissional do assistente social a partir das configurações da política de ensino superior em curso no Brasil. Esta análise perpassa o estudo do desenvolvimento do Serviço Social e da construção do aparato teórico-metodológico da profissão, bem como os dilemas existentes na relação teoria e prática. Foram entrevistados oito assistentes sociais em Ribeirão Preto, atuantes nas áreas sócio-jurídica, saúde, previdência social e assistência social. A partir das reflexões realizadas à luz da discussão teórica e do conteúdo das entrevistas, o presente estudo discorre sobre os conflitos vivenciados pelos profissionais entrevistados no seu trabalho profissional cotidiano, enfatizando as dificuldades com relação ao referencial teórico-metodológico que os orienta e abarcando a visão dos mesmos sobre sua formação, suas condições de trabalho e a conjuntura brasileira. Ao longo do estudo foi possível perceber que as configurações da formação e as condições objetivas da realidade em que os assistentes sociais estão trabalhando interferem diretamente nas suas percepções sobre as questões abordadas, determinando um contexto em que não se identifica um referencial teórico-metodológico específico que orienta...
Keywords: Serviço social - Prática; Formação profissional - Brasil; Assistentes sociais - Ribeirão Preto (SP); Trabalho profissional; Prática profissional; Social service